ESTABLISHING A TEACHING PRACTICE PROCESS THROUGH TRAIN THE TRAINER PROGRAM IN THE SINABUNG VOLCANO™s EXCLUSION ZONE: A QUALITATIVE CASE STUDY IN MARDINGDING VILLAGE AT THE DISTRICT OF KARO - Sibarani, Choms Gary Ganda Tua; Zainal, Andri; Herliani, Rini (Journal of Community Research and Service, 2018)
AbstractThis paper discusses the outcomes resulted from efforts in optimizing the implementation of a teaching practice process in a current/post-disaster area. The purpose of this study is to implement the Train-the-Trainer program for local youth as educational agents to pupils in Mardingding Village and in other villages around those affected by the disaster so that the learning spirit of students is maintained. Based on the data analysis using the rapid mapping method with the Rapid Spiral Boehm model, it can be concluded that the implementation and existence of the Train the Trainer program has a positive influence on students' interest in learning activities that are not only focused on activities within the school but also outside the school. The relatively good achievement of learning outcomes after the implementation of the train the trainer program underscores interesting findings in which regions experiencing disasters can still meet learning outcomes with all the inherent limitations of the condition of the affected area. This applied research has limitations, namely focusing on qualitative data analysis so that the interpretation of the findings obtained also has relatively specific implications for the coverage of the Mardingding Village area in the Tiganderket District in Karo District.Keywords: Train the Trainer Program, Teaching Practice Process, Disaster Area, Mardingding Village, Rapid Spiral Boehm.